Evaluation of Inflammatory Markers in the Blood of Colorectal Cancer Patients - Lazem, Haneen S.; Sharba, Zahraa A.; Sulaiman, Ghassan M.; Hasan, Zainab F. M. (Iraqi Journal of Science, 2026)
The incidence of colorectal cancer (CRC) is rising globally, accompanied by a high mortality rate. Systemic inflammation is believed to significantly contribute to CRC development, highlighting the need for accessible, reliable, and cost-effective tools to assess patients' inflammatory status. This study aimed to evaluate liver and renal functions and the changes in blood cell-based inflammatory markers related to CRC. This cross-sectional case-control study included 60 colorectal cancer (CRC) patients and 30 healthy controls.  Complete blood counts were performed using an automated analyzer. The blood cell-based inflammatory markers include the platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), and neutrophil × platelet/lymphocyte × hemoglobin ratio (NP/LHB). SII and NP/LHB were significantly elevated in patients with CRC compared with controls (probability [p] = 0.029 and 0.043), while NLR and PLR showed no significant differences (p = 0.486 and 0.39). Tumor stage, grade, and site, along with disease duration, may impact the levels of PLR, NLR, SII, and NP/LHB. The levels of liver function parameters alanine transaminase (ALT) and aspartate transaminase (AST) were significantly higher in patients than in controls (p = 0.013 and 0.019, respectively), while alkaline phosphatase levels showed non-significant differences (p = 0.197). The renal function parameter serum creatinine showed significantly elevated levels in patients compared to controls (p = 0.048), while the levels of blood urea nitrogen were not significantly different (p = 0.39). Changes in the level of these blood-cell-based inflammatory indicators may be influenced by tumor stage, tumor grade, disease duration, and tumor site. Significantly elevated levels of ALT, AST, and creatinine were also associated with CRC.